Integrative Analyses of Transcriptome Sequencing Identify Functional miRNAs in the Chicken Embryo Fibroblasts Cells Infected With Reticuloendotheliosis Virus - Zhai, Jie; Gao, Chang; Fu, Lisheng; Jing, Long; Dang, Shengyuan; Zheng, Shimin (Frontiers in Genetics, 2018)
In this study, we found a much higher proportion of reticuloendotheliosis virus (REV) infected chicken embryo fibroblasts (CEF) were in active cell division phase than that of control cells which indicated that REV can affect the fate of CEF. So, we performed high-throughput sequencing and transcriptomic analysis to identify functional miRNAs, in order to figure out the possible mechanism in the interaction of REV with CEF. In total, 50 differentially expressed miRNAs (DEmiRNAs) were identified. Then target genes of DEmiRNAs were predicted and identified by transcriptome profile results. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment were conducted to analyze the identified target genes of miRNAs which showed that metabolism, cell cycle, and apoptosis were the most related pathways involved in infection of REV. We analyzed the genes related to cell cycle which indicated that CyclinD1-CDK6 complex played an important role in regulating the transition of the cell cycle from G1 phase to S phase during REV infection. Fluorescence microscope identification showed that REV inhibited the apoptosis of CEF which was in accordance with transpriptome results. A novel miRNA, named novel-72 was found, KEGG analysis was conducted to predict the biological function of its target genes which showed that those target genes were significantly enriched in mTOR signaling pathway and functioned to promote cell cycle and cell growth during the REV infection. In conclusion, REV could induce the up-regulation of cell metabolism, cell cycle and mTOR signaling pathway while inhibit apoptosis of the cell.